2018
DOI: 10.1016/j.jvs.2017.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive medication adherence in chronic type B aortic dissection is an important consideration in the management debate

Abstract: Medical management remains the mainstay of treatment in uncomplicated TBAD; however, the majority of patients are poorly adherent to their antihypertensive medications. The merits of thoracic endovascular aortic repair in TBAD are argued, and poor adherence is an important factor in the debate; one cannot robustly compare two strategies when half of a treatment group may not be receiving the stated intervention. To develop an evidence-based treatment strategy for TBAD, we must take into account the direct and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Morisky Medication Adherence scale scores were distributed into high (41.4%), intermediate (33.6%), and low (25.0%) adherence. This distribution was relatively consistent with prior studies indicating overall high rates of nonadherence to prescribed medications, [7][8][9][10][11] although variation can be attributed to differences in definition, measurement of adherence, and patient population. A study by Martin et al similarly used MMAS-8 to measure adherence to antihypertensives in chronic type B aortic dissection patients and found a remarkably analogous distribution at high (43%), intermediate (36%), and low (21%) adherence.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Morisky Medication Adherence scale scores were distributed into high (41.4%), intermediate (33.6%), and low (25.0%) adherence. This distribution was relatively consistent with prior studies indicating overall high rates of nonadherence to prescribed medications, [7][8][9][10][11] although variation can be attributed to differences in definition, measurement of adherence, and patient population. A study by Martin et al similarly used MMAS-8 to measure adherence to antihypertensives in chronic type B aortic dissection patients and found a remarkably analogous distribution at high (43%), intermediate (36%), and low (21%) adherence.…”
Section: Discussionsupporting
confidence: 87%
“…A study by Martin et al similarly used MMAS-8 to measure adherence to antihypertensives in chronic type B aortic dissection patients and found a remarkably analogous distribution at high (43%), intermediate (36%), and low (21%) adherence. 10 Younger age was significantly associated with low adherence. This is similar to a cardiology study that identified age <65 as an independent predictor of low adherence, 13 and another vascular study that demonstrated younger patients were less adherent to American Heart Association/American College of Cardiology (AHA/ACC) guideline-recommended therapies: aspirin, statin, angiotensin-converting enzyme inhibitor, and smoking cessation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The importance of good blood pressure control cannot be overestimated as the major component of conservative management; from trials such as the INvestigation of STEnt grafts in patients with type B Aortic Dissections (INSTEAD) and Acute Dissection Stent Grafting or Best Medical Treatment (ADSORB), we have learned that the majority of patients required at least three different antihypertensive medications to achieve a satisfactory blood pressure control [16]. Moreover, a recent observational study performed outside of a trial setting demonstrated that the majority of patients adhere poorly to a combination antihypertensive therapy [17]. Guidelines from the American College of Cardiology and the European Society of Cardiology suggest further studies should be undertaken to refine the therapeutic approaches required for early medical management in patients with type B aortic dissection [8,11].…”
Section: Optimal Medical Treatment (Omt)mentioning
confidence: 99%
“…64,65 Unfortunately, adherence to anti-hypertensive medications is an issue. 66 CTA is the imaging of choice. In younger patients, especially lifetime radiation exposure because of multiple CTA should be considered in follow-up imaging.…”
Section: Follow-upmentioning
confidence: 99%